L-ARGININE SUPPLEMENTATION IN ANTIHYPERTENSIVE THERAPY: A NOVEL APPROACH TO ENDOTHELIAL AND METABOLIC CORRECTION IN INSULIN-RESISTANT PATIENTS - Khrebtii, Halyna (European Science, 2025)
This study explored vascular motor responses, as well as lipid and carbohydrate metabolism in patients with arterial hypertension and insulin resistance, identifying key features of endothelial dysfunction and novel therapeutic strategies. The clinical ef